Peran Deborah Berdasarkan Kitab Hakim-Hakim 4 dan Implikasinya Bagi Guru Kristen Masa Kini - Ba Si, Silva; Rimbe, Aris D; Alfredo Tampilang, Petra Harys (Sekolah Tinggi Teologi Injili Indonesia Ambon, 2025)
This research explains the role of women in Judges 4 in the context of modern Christian teachers. The background of this writing is to find out the role of women in the book of Judges 4. The character discussed in the book of Judges 4 is Deborah. The method used in this research is qualitative method. The qualitative method used is literature study. The author uses books, journals, and literature that support the writing. This study found that Deborah had three roles, namely as a prophetess, wife, and judge. Deborah's example for modern Christian teachers is as a teacher, helper, and good listener.